2016
DOI: 10.1021/acs.jpcc.6b00812
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Investigations of Ferrocene-Terminated Self-Assembled Monolayers: Electronic State Changes Induced by Electric Dipole Field of Coadsorbed Species

Abstract: Ferrocene-terminated self-assembled monolayers (SAMs) have been widely studied in the past quarter century to reveal the electrochemical properties of chemically modified electrodes. It has been well-known that the formal potential of the system strongly depends on the local environment of the ferrocene moiety. Although electronic states of ferroceneterminated SAMs should directly affect the electrochemical properties, knowledge concerning electronic structures with respect to different local environment is ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…This peak is predominantly ascribed to the six electrons in the 3d orbitals of Fe, which form the HOMO of Fc, giving (a 1g ) 2 (e 2g ) 4 as the electronic configuration. 12,58 Following oxidation to Fc + , the HOMO is expected to shift to toward higher binding energy with Fc + possessing the electronic configuration (a 1g ) 2 (e 2g ) 3 . 45 It is noteworthy that Yokota et al observed nearly matching shifts in the Fe 2p 3/2 peak from XPS and the HOMO peak from UPS of Fc SAMs with different electron donating groups ascribed to the Fc HOMO being localized with the Fe atom.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This peak is predominantly ascribed to the six electrons in the 3d orbitals of Fe, which form the HOMO of Fc, giving (a 1g ) 2 (e 2g ) 4 as the electronic configuration. 12,58 Following oxidation to Fc + , the HOMO is expected to shift to toward higher binding energy with Fc + possessing the electronic configuration (a 1g ) 2 (e 2g ) 3 . 45 It is noteworthy that Yokota et al observed nearly matching shifts in the Fe 2p 3/2 peak from XPS and the HOMO peak from UPS of Fc SAMs with different electron donating groups ascribed to the Fc HOMO being localized with the Fe atom.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Ferrocene-terminated alkanethiol self-assembled monolayers (Fc SAMs) on Au are an ideal model system owing to their practical significance and versatility with structural modifications. The corresponding ferrocene/ferrocenium (Fc/Fc + ) redox couple consists of single electron transfer and ion pairing reactions with anions (X – ) as follows: …”
Section: Introductionmentioning
confidence: 99%
“…Previous electrochemical studies have utilized Fc-terminated alkanethiol self-assembled monolayers (SAMs) where the strong chemical interaction between the sulfur and gold anchors the molecule onto the electrode surface. ,,,,,,,,,, However, it is known that Fc-terminated alkanethiol SAMs undergo structural fluctuations and changes in SAM orientation during redox reactions, , ,, making it difficult to probe the unperturbed electronic state during redox reactions with EC-STM. Furthermore, in order to investigate the unperturbed redox reaction of Fc, it is desirable to strategically place Fc moieties solvated with electrolyte solution, rather than surrounded by other organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The 1.6 eV peak in the pristine sample has been attributed to the HOMO states of ferrocene spatially localized on Fe 2+ ion. [53][54][55][56] This peak disappears when the electrode is emersed at the higher potential (the Fe 3+ state). This means that as the molecule is oxidized, the ferrocene becomes positively charged and the entire orbitals shift toward the higher binding energy side.…”
Section: Ex Situ Measurementsmentioning
confidence: 99%